Accessing the Subsurface Biosphere Within Rocks Undergoing Active Low‐Temperature Serpentinization in the Samail Ophiolite (Oman Drilling Project). Issue 10 (28th September 2021) - Templeton, Alexis S.; Ellison, Eric T.; Glombitza, Clemens; Morono, Yuki; Rempfert, Kaitlin R.; Hoehler, Tori M.; Zeigler, Spencer D.; Kraus, Emily A.; Spear, John R.; Nothaft, Daniel B.; Fones, Elizabeth M.; Boyd, Eric S.; et al.
Abstract: The Oman Drilling Project established an "Active Alteration" multi‐borehole observatory in peridotites undergoing low‐temperature serpentinization in the Samail Ophiolite. The highly serpentinized rocks are in contact with strongly reducing fluids. Distinct hydrological regimes, governed by differences in rock porosity and fracture density, give rise to steep redox (Eh +200 to −750 mV) and pH (pH range 8.5–11.2) gradients within the 300–400 m deep boreholes. The serpentinites and fluids host an active subsurface ecosystem. Microbial cell abundances in serpentinite vary at least six orders of magnitude, from ≤3.5 × 10 1 to 2.9 × 10 7 cells/g. Low levels of biological sulfate reduction (2–1, 000 fmol/cm 3 /day) can be detected in rock cores, particularly in rocks in contact with reduced groundwaters with pH < 10.5. Thermodesulfovibrio is the predominant sulfate reducer identified via metagenomic sequencing of adjacent groundwater communities. We infer that transport and reaction of microbially generated sulfide with the serpentine and brucite assemblages gives rise to optical darkening and sulfide overprinting, including the formation of tochilinite‐vallerite group minerals, potentially serving as an indicator that this system is inhabited by microbial life. Olivine mesh‐cores replaced with ferroan brucite and minor awaruite, abundant veins containing hydroandradite garnet and polyhedral serpentine, and late‐stage carbonate veins are suggested as targets for future spatially resolved life‐detection investigations. The high‐quality whole‐round core samples that have been preserved can be further probed to define how life distributes itself and functions within a system where chemical disequilibria are sustained by low‐temperature water/rock interaction, and how biosignatures of in situ microbial activity are generated. Plain Language Summary: Ultramafic rocks undergoing water/rock interaction, and storing fluids that are far from chemical equilibrium, may be one of the most common habitats in our solar system. Through the Oman Drilling Project we collected >1 km of intact serpentinite in contact with groundwaters. These cores capture parts of the rock‐hosted biosphere and show how cells are distributed within serpentinites that vary in their mineralogical, physical and chemical properties. The cores are also biologically active, enabling us to detect specific metabolisms, such as when microorganisms combine hydrogen as reductant and sulfate as an oxidant to fuel their metabolism. Although the distribution of microbial cells in the rock cores is very heterogeneous, there are many intervals where the abundance of cells constitutes robust biomass. In the deeper cores, slow, albeit detectable, microbial sulfate reduction proceeds. We suggest that this pervasive biological activity releases byproducts such as sulfide that can react with the serpentinite and change the optical and chemical properties of the rocks. The feedbacks between the rock alteration and microbial activity produce markers that enable us to focus our search for rock‐hosted life and any specific biosignatures it may produce on Earth and perhaps on other planetary bodies. Key Points: Highly serpentinized subsurface rocks exhibit steep redox gradients and host microbial cell abundances that vary >6 orders of magnitude Low rates of microbial sulfate reduction in rock cores are inferred to result in optical darkening and sulfide overprinting of the mineralogy Widespread andradite garnet, abundant ferroan brucite, and rare carbonate are targets for future spatially resolved life‐detection efforts